Sztuka radosna albo radość w dźwięku - POCIEJ, † Bohdan (Ethos. Kwartalnik Instytutu Jana Pawła II KUL, 2011)
Music is called to reveal the beauty of being and, as such, to infuse joy into the human soul. One can say that in the respect of joy music differs from the other arts: in poetry, painting, sculpture or architecture joy appears as a merely occasional visitor, while in music it feels «at home.» In the current article, the author first analyzes the forms and means of expressing joy in music and then presents how they evolved in its history. There are three constitutive factors affecting expression of joy in music, namely: the movement, the melos and the sound. Additionally, one can distinguish its four main sources, namely, (1) the pure joie de vivre, or vitality that lies at the basis of music creating energies, (2) the joy of love, which is the first existential principle of being and the fundamental mode of existence, (3) the joy of artistic creation in its initial, spontaneous phase, when the artist experiences a powerful influx of artistic power, regardless of the shape a given work is going to assume, and (4) religious faith, conceived of as an act of spiritual freedom (the Christian faith informs and enlivens four masterpieces of modern music: Monteverdi’s Vespro..., Bach’s Mass in B minor, Haendel’s Messiah and Beethoven’s Missa Solemnis. Abstracts 346 In 17th century Europe composers believed that music was indeed the speech of sounds and, as such, was to manifest emotions. In a way, it was to follow the rules of verbal rhetoric and thus produce its own rhetoric of sound, to become a kind of language in which particular passions are assigned appropriate acoustic motifs. The apogee of this development can be seen in the rich and diverse output of Johann Sebastian Bach. In his works, which reflect the serene and bright sides of the human existence, sublimating and variously transforming them into musical sounds, joy is articulated in versatile ways and it demonstrates various shades. It is inspired above all by God, by human presence in the world, by the world as such and by music itself, which is perceived as a manifestation of the pure energy of life. The apogee of «joyous knowledge» in 18th century music was preceded, in the 17th century, by a lengthy period in which music tended towards the “pessimistic” realms of joylessness and melancholy rather than towards the “optimistic” ones of cheerfulness and joy. However, the form−giving energy resulting in the expression of joyfulness, was originally manifested in early 17th century in the compositions of Claudio Monteverdi, the first genius of modern music, and maintained by his successors, the founders of Italian opera schools. It was there, in its communion with poetry and theatre, that music evolved so rapidly, creating its own, diverse, «affected» speech of sounds. In the era of Bach, as well as in the time immediately after his death, usually referred to as the Vienna classicism, although it was actually the pre−Romantic period, the «joyful knowledge» dictated the prevailing pattern in the creation of music, which followed the aesthetic standards of the time: the focus on pleasure and playfulness. The spiritual space in the late Enlightenment was informed with joyous energies which surfaced in the creation of music, exhibiting its power, continuity and intensity unmatched in the later periods. As a result, musical masterpieces were created, the most outstanding of them being Haydn’s symphonies, quartets and trios, as well as Mozart’s symphonies, quartets, quintets, trios, piano concertos and operas. In mid−18th century the rhetorical and rationalistic «speech of sounds» characteristic of the Baroque period is transformed into a more intuitive «speech of emotions.» Romantic music par excellence (represented by Schubert, Berlioz, Schumann, Mendelssohn and Chopin) is marked by a harmony of various emotional qualities and their oscillation between the poles of «light» and «darkness.» The founding sonic substance of this interplay of emotions and of the changing of the moods was provided by the contrast between the major and minor keys, which ruled in music from the twilight of the Renaissance to the end of the Romantic period. Yet in Romantic and late Romantic music, which exhibited an extraordinary diversity of the means of expression and emotional shades, also the expression of joy became ambiguous, thus losing the prevailing role it enjoyed throughout the 18th century. Therefore one can all the more marvel at the output of Ludwig van Beethoven, the ingenious protagonist of the Romantic age, whose music, from his first compositions to the very last ones, is enlivened by the same powerful stream of form−giving energy. As a result, the expression of «bright» joy in his works seems to prevail over that of sadness or agitation. At the turn of the 20th century, a new, impressionist world of music was created by Claude Debussy in his piano works manifesting a particular brightness of Abstracts 347 sound, as well as an interplay of various shades of «light» and «darkness,» and resulting in the overall attitude of happiness and joyfulness. In the anti−Romantic currents of the new music of the 20th century (such as vitalism, neofolklorism and neoclassicism), represented, among others, by Ravel, Stravinsky, Bar− tók, and Prokofiev, joy in its pure quality was reborn in clear references to the 18th century music (through joke and comedy, parody, pastiche and grotesque). Summarized by Cezary Ritter Translated by Dorota Chabrajska